Friday

April 18, 2014

April 18, 2014

Posted by **Jennifer** on Sunday, January 18, 2009 at 5:44pm.

-5^2 + 2[64 /(6 - 10)^2] =

-5^2 + 2[64/(-4)^2]=

-5^2 + 2[64/16]=

-25 + 2 [64/16]=

-25 + 2 (4)=

-25 +8

= -17

Is this Corect?

- Intermediate Algebra -
**jess**, Sunday, January 18, 2009 at 6:04pmyes, i think that you are correct :)

**Related Questions**

Algebra B - x^2 - 5/2x + 25/16 = -4 + 25/16 = (x-5/4)^2 = -64/16 + 25/16 = (x-5/...

algebra - what number is used to complete the square for the equation y^2 + 16...

algebra - What number is used to complete the square for the equation y^2 + 16...

Please check answers) - Perform the indicated operations and simplify the result...

Pre-Calculus - Could someone check my answers? 27. (16/9)^2/3 = 64/27 28. (49/25...

Algebra - I am trying to figure out how to evaluate 100^-3/2. I'm going by the ...

math - Tell whether the sequence is geometric. Explain why or why not. 1. 4, 16...

chemistry - First of all, you need to know how many g of Mg actually reacted in ...

Math - Place the following number in order from Least to Greatest. A. 64.34 B. ...

statistics - I have: E=2.4/64=8/64.64=0.125 95% confidence interval ranges from ...